2012
DOI: 10.1136/postgradmedj-2010-74245
|View full text |Cite
|
Sign up to set email alerts
|

Improving outcome in severe trauma: trauma systems and initial management—intubation, ventilation and resuscitation

Abstract: Severe trauma is an increasing global problem mainly affecting fit and healthy younger adults. Improvements in the entire pathway of trauma care have led to improvements in outcome. Development of a regional trauma system based around a trauma centre is associated with a 15-50% reduction in mortality. Trauma teams led by senior doctors provide better care. Although intuitively advantageous, the involvement of doctors in the pre-hospital care of trauma patients currently lacks clear evidence of benefit. Poor ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 59 publications
2
26
0
1
Order By: Relevance
“…It has been shown that more aggressive initial TBI management has led to improved patient outcomes (Harris et al . , Prabhakar et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that more aggressive initial TBI management has led to improved patient outcomes (Harris et al . , Prabhakar et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…One of the most important nursing roles when caring for TBI patients is to ensure that accurate neurological assessments are conducted and communicated in a timely manner so treatments can be initiated promptly. It has been shown that more aggressive initial TBI management has led to improved patient outcomes (Harris et al 2012, Prabhakar et al 2014. Patients with TBIs may have sudden increased intracranial pressure, instability or changes in balance or vision that require immediate therapy lest lifelong Table 1 Literature inclusion and exclusion criteria.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…39,40 Despite the fact that trauma center personnel routinely record demographic, treatment, and outcome data of their patients, surprisingly few studies have published airway management and fluid and blood resuscitation data. 39,40 Despite the fact that trauma center personnel routinely record demographic, treatment, and outcome data of their patients, surprisingly few studies have published airway management and fluid and blood resuscitation data.…”
Section: Discussionmentioning
confidence: 99%
“…Clear leadership and coordination must exist across regions and within hospitals 118. When managing individual patients the evidence base remains poor119 and large high quality trials remain the exception.…”
Section: Discussionmentioning
confidence: 99%